Leadership with Integrity - Nkemdili, Nnonyelu Au (Practicum Psychologia, 2020)
Many organisations have been afflicted with leadership deficits. In Nigeria, and other countries in Sub Saharan Africa, carcasses of failed companies, and businesses litter the socio-economic landscape. The challenge of leadership at all levels has become more profound today. The paper emphasizes the need to develop a new leadership ethos, if struggling businesses will come out of their current quagmire. This new leadership narrative ties integrity inextricably to leadership. It argues that integrity is the cornerstone of leadership and that organisations in the future are unlikely to endure, if these firms, associations are bereft of integrity.